Improved one-dimensional model potentials for strong-field simulations - Majorosi Szilárd (PHYSICAL REVIEW A, 2018)
Based on a plausible requirement for the ground-state density, we introduce an alternative one-dimensional (1D) atomic model potential for the 1D simulation of the quantum dynamics of a single active electron atom driven by a strong, linearly polarized few-cycle laser pulse. The form of this density-based 1D model potential also suggests improved parameters for other well-known 1D model potentials. We test these 1D model potentials in numerical simulations of typical strong-field physics scenarios and we find an impressively increased accuracy of the low-frequency features of the most important physical quantities. The structure and the phase of the high-order harmonic spectra also have a very good match to those resulting from the three-dimensional simulations, which enables one to fit the corresponding power spectra with the help of a simple scaling function.